Tantangan dan Solusi Ma’had dalam Pembentukan Karakter Mahasantri pada Era Digital - Arrosidah, Orva Farihah (Proceeding of International Conference on Islamic Education (ICIED), 2025)
As an Islamic educational institution responsible for shaping the character of mahasantri, Ma'had encounters several challenges in the digital era. These issues include weakened discipline, limited Islamic-based digital literacy, and declining digital ethics. These issues have been caused by unrestricted access to information, intensive use of digital media, and shifting social interaction patterns. This study aims to identify the main problems faced by ma’had in the digital era. To conduct this research, a qualitative literature review was used to examine between 16 and 30 national journals published between 2021 and 2025. The focus of these journals was Islamic education, digital literacy, character formation, and Islamic boarding school-based learning. These sources were selected based on specific criteria, such as thematic relevance, publication date, and methodological credibility. For the purpose of digital character development, the data was combined through thematic analysis to identify key issues and suggested solutions. The study's findings reveal three main issues: (1) digital ethics that affects online ethics and actions; (2) Islamic digital literacy which makes it difficult for students to analyze and assess online information; and (3) discipline and time management that is ineffective due to the use of gadgets that is ineffective.  This study further indicates that this issue can be resolved by developing an Islamic digital literacy curriculum that enhances Islamic digital literacy. In conclusion, this study provides theoretical and practical contributions by providing an integrated framework for character formation in the digital era of Islamic education. It also emphasizes the role of Ma'had as a relevant and strategic institution in cultivating ethical, disciplined, and digitally literate students in the modern era.